PENGUATAN BRANDING SDK COR JESU MALANG DENGAN OPTIMALISASI WEBSITE DAN PEMANFAATAN DIGITAL MARKETING - Christmantara, Vinno (Asawika : Media Sosialisasi Abdimas Widya Karya, 2024)
SDK Cor Jesu Malang faced challenges in managing its website, including an unattractive design, difficulties in updating content, and low SEO rankings, which resulted in poor branding. The community service team from Widya Karya Catholic University (UKWK) Malang provided a solution by developing a new website using the CMS WordPress and Divi Builder. Additionally, the team conducted basic digital marketing training, training on using the website built with Divi Builder, and content creation. The results were significantly impactful for SDK Cor Jesu, including improved SEO rankings that allowed the website to appear on Google’s first page, easier access to information for parents, and a more responsive, attractive, and user-friendly interface. The SDK Cor Jesu Malang website now serves not only as a communication tool but also as a promotional medium that enhances the school’s branding. With better branding, SDK Cor Jesu’s efforts to attract prospective students have been realized. This community service activity also fostered collaboration in empowering educational institutions, involving students and lecturers from UKWK’s Information Systems program, to tackle digital challenges effectively.